Accounting in the Administration of Large Business Enterprises (Book). - Winter, Sidney G.; Bailey, Geo. D. (The Accounting Review, 1944)
Abstract Reviews the book "Accounting in the Administration of Large Business Enterprises," by Charles A. Heiss.